Pembrolizumab in classical Hodgkin’s lymphoma - Maly, Joseph (Eur J Haematol, 2016)
Pembrolizumab is a humanized monoclonal antibody directed against programmed cell death protein 1 (PD-1), a key immune-inhibitory molecule expressed on T cells and implicated in CD4+ T-cell exhaustion and tumor immune-escape mechanisms. Classical Hodgkin’s lymphoma (cHL) is a unique B-cell malignancy in the sense that malignant Reed–Sternberg (RS) cells represent a small percentage of cells within an extensive immune cell infiltrate. PD-1 ligands are upregulated on RS cells as a consequence of both chromosome 9p24.1 amplification and Epstein–Barr virus infection and by interacting with PD-1 promote an immune-suppressive effect. By augmenting antitumor immune response, pembrolizumab and nivolumab, another monoclonal antibody against PD-1, have shown significant activity in patients with relapsed/refractory cHL as well as an acceptable toxicity profile with immune-related adverse events that are generally manageable. In this review, we explore the rationale for targeting PD-1 in cHL, review the clinical trial results supporting the use of checkpoint inhibitors in this disease, and present future directions for investigation in which this approach may be used.